Economic evaluation of Wolbachia deployment in Colombia: A modeling study - Donald S. Shepard; Samantha R. Lee; Yara A. Halasa-Rappel; Carlos Willian Rincon Perez; Arturo Harker Roa (PLoS ONE, 2025)
Background and aims Wolbachia are bacteria that inhibit dengue virus replication within the mosquito. A cluster-randomized trial in Indonesia found Wolbachia reduced virologically-confirmed dengue cases by 77.1%. Previous models predicted Wolbachia to be highly cost-effective in Indonesia, Vietnam, and Brazil. To inform decisions about future extensions in Colombia, we performed economic evaluations of potential Wolbachia deployments in 11 target cities. Methods We assembled the numbers and distribution by severity of reported dengue cases from Colombia’s national disease surveillance system and the health service provision registry (RIPS). An epidemiological panel of three experts estimated the shares of dengue that were non-medical, under-reported, or misreported as another disease. We determined costs (in 2020 US dollars at market prices) of treating dengue illness from the benchmark insurance tariff and RIPS data on treatment services per symptomatic dengue case. Our central estimates projected 10 years of efficacy and focused on Cali, the target city with the highest number of dengue cases. Results For Cali, we estimated a net health-sector savings of US$4.95 per person and averting 369 disability-adjusted life years (DALYs) per 100,000 population. From a societal perspective, at 10 years Wolbachia deployment is expected to have highly favorable benefit-cost ratios, with benefits per dollar invested of US$5.50 in Cali and US$4.68 over all target cities. Conclusions Over 10 years, Wolbachia is highly beneficial on economic grounds, and almost universally cost saving. The Wolbachia program’s economic benefits exceeded its costs in all 11 cities. The program’s savings in healthcare costs alone would more than offset deployment costs nationally and in 9 of 11 target cities. Wolbachia is likely to be the most cost-effective or cost-saving dengue control option in municipalities with both high incidence of dengue and high population density, whereas areas with high dengue incidence but low population density should consider vaccination.